Lignin-degrading filamentous fungi isolated from Calamagrostis nitidula Pilg. - Laura, Janet (2009)
We isolated fungi with ligninolytic activity of the forage plant Calamagrostis nitidula Pilg. (Poaceae). The mini- mum Czapeck medium containing lignin (0,2%) as carbon source, was inoculated with fractions of C. nitidula. Subsequently, the fungus developed were isolated in potato dextrose agar (PDA) and identified according to their macroscopic and microscopic characteristics. The following genus were isolated and identified: Alternaria, Ulocladium, Trichoderma, Cephalosporium, Helicomyces Mucor and Aspergillus. Degradation of lignin was determined qualitatively and quantitatively, by inoculating each strain obtained in tubes with Czapeck medium with 0,2% lignin and 1% glucose. Only the PD5F strain identified as Aspergillus melleus Yukawa was ligninolytic activity.